A New Absolute Encoder Design Based on Piecewise Pseudo-Linear Signals - Celik, Emre; Obdan, Atiye Hulya (IEEE sensors journal, 2024)
In this article, a new absolute encoder design based on a microcontroller (μC), which is cheap and simple to manufacture and produces high-precision linear output, is presented. Our demodulation algorithm is based on the linearization of highly linear regions around the midpoints of sinusoidal signals generated by sensors. In this study, we manufactured the encoder disk ourselves, and by adjusting the sensor parameters optimally, we successfully obtained more linear signals compared to the signals produced by conventional sine-cosine encoders. The obtained pseudo-linear sections are made more linear through third-order polynomial regression. Additionally, with the help of an extra track on the disk and two sensors, segment-specific linearization has been applied to pseudo-linear segments that are not exactly the same one-to-one. This approach ensures the high accuracy of the encoder, unlike studies that apply the same correction to each sinusoid generated. In addition, the system has gained the absolute encoder function, with a simpler disk structure that is easier to manufacture than the code disks of traditional absolute encoders. The performance of the proposed encoder is verified with an optical encoder arrangement of 2x10 5 pulses per revolution, and an error of 0.00203° per revolution is obtained.